2010
DOI: 10.1097/acm.0b013e3181c4782b
|View full text |Cite
|
Sign up to set email alerts
|

Medical Studentsʼ Experiences of Moral Distress: Development of a Web-Based Survey

Abstract: Medical students frequently experience moral distress. Our survey can be used to measure aspects of the learning environment as well as individual responses to the environment. The variation found among student responses warrants further investigation to determine whether students at either extreme of moral distress are at risk of burnout or erosion of professionalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 17 publications
6
92
0
3
Order By: Relevance
“…The main purpose behind this comparison was to appraise whether these student cohorts engaged in different types of academic dishonesty and to consider attitudes to ethical dilemmas between professional contexts of learning. No articles were found that compared the extent of academic dishonesty between these two cohorts, even though considerable research has examined the extent of the problems within the disciplines (Ng et al 2003;Papadakis et al 2004;Bilic-Zulle et al 2005;Whitley & Starr 2010;Wiggleton et al 2010).…”
Section: Practice Pointsmentioning
confidence: 99%
“…The main purpose behind this comparison was to appraise whether these student cohorts engaged in different types of academic dishonesty and to consider attitudes to ethical dilemmas between professional contexts of learning. No articles were found that compared the extent of academic dishonesty between these two cohorts, even though considerable research has examined the extent of the problems within the disciplines (Ng et al 2003;Papadakis et al 2004;Bilic-Zulle et al 2005;Whitley & Starr 2010;Wiggleton et al 2010).…”
Section: Practice Pointsmentioning
confidence: 99%
“…For similar reasons, moral distress is also prevalent among house staff. [4][5][6][7] Situations that often produce moral distress include aggressive treatment of dying patients, witnessing or participating in substandard care, and involvement in the withholding of information from patients. 6 Clinicians' levels of moral distress often crescendo around a crisis and then fall after the precipitating incident has resolved.…”
Section: Moral Distressmentioning
confidence: 99%
“…Wiggleton et al [32] found that female medical students reported witnessing distressing dilemmas significantly more frequently than male medical students, although males tended to report experiencing greater distress than females with each dilemma they encountered [32]. In our questionnaire study of 2,397 medical students in the United Kingdom (UK), we found that males typically classified themselves as experiencing no distress, whereas females typically categorized themselves as experiencing distress [2].…”
Section: Moral Distress and Its Correlatesmentioning
confidence: 63%